Novel method for the selection of time hopping codes for UWB communication systems - Singh, Rajendra; BS Jassal, Dr (International Journal of Engineering and Technology, 2018)
This work investigates the BER performance of existing code families of Frequency Hopping (FH) codes as Time Hopping (TH) codes in multiuser UWB communication environment and provides a novel method for the selection of TH codes. The performance of codes has been validated in AWGN channel for single user and further validated over multiuser environment. A significant improvement in performance has been observed over random codes. It is validated that selection of better TH codes reduces the MUI and improves the overall performance of the communication system and FH codes with better correlation properties can be used as TH codes in multiuser UWB communication system.Â Â